PENGARUH SENAM KEGEL DAN REBUSAN DAUN SIRIH TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POSTPARTUM NORMAL - Yustina Novelia Jatining Purnamasari; Desi Soraya; Danny Putri (Midwifery Science Care Journal, 2024)
Perineal tear happens on all pervaginam deliveries in Semarang. The prevalence is 53%. Postpartum mothers with perineal tears should receive excellent care to prevent birth canal infection. Perineal tear medication includes both pharmacological and non-pharmacological medications. The non-pharmacological medication includes early mobilizations, such as kegel calisthenics and the administration of boiled betel leaf to wipe the perineal tear. This research determined the influence of Kegel calisthenics and the administration of boiled betel leaf to cure the perineal tear of normal postpartum mothers in the working area of Ngesrep health care. This quasi-experimental research used a posttest-only control group design. The population consisted of pervaginam-postpartum mothers in the working area of Ngesrep health care in July 2022. The applied sampling technique was purposive sampling. The obtained sample was 32 respondents. The applied instrument was an observation sheet. The data analyses included univariate and bivariate analyses (chi-square). The result obtained a p-value of 0.013, lower than 0.05 with OR = 7.22. Thus, H0 was denied while Ha was accepted. The value indicated that kegel calisthenics and the administration of boiled betel leaf influenced the recovery progress of perineal tear in the normal-postpartum mothers in the working area of Ngesrep health care. The applied Kegel calisthenics and the administration of boiled betel leaf were 7.222 quicker to cure the scar than the implementation of Kegel calisthenics. The results recommended applying Kegel calisthenics and boiled betel leaf for postpartum mothers autonomously as the alternative to cure the perineal tear. Kegel calisthenics and the boiled betel leaf were efficient and affordable to apply in the surrounding environment.